AQUAPONICS AS A SOLUTION FOR FAMILY FOOD SECURITY IN URBAN AREAS - Garnida, Yudi (Jurnal Multidisiplin Sahombu, 2023)
Food security is one of the main challenges in urban areas, where land is limited and access to food resources is limited. Aquaponics, as an integrated system of aquaculture and hydroponics, has been recognized as an innovative solution to meet food needs in urban areas by utilizing land efficiently and optimizing the use of water resources. This study aims to evaluate the potential of aquaponics as a solution to family food security in urban areas. This research uses a qualitative approach with descriptive methods. The results of this study indicate that aquaponics has significant potential in increasing family food security in urban areas. The aquaponic system is capable of simultaneously producing a wide variety of vegetables and fish, providing a balanced source of protein and nutrition for the family. In addition, aquaponics can also be applied in urban environments that have limited land by using vertical spaces or controlled container systems. The conclusion from this research is that aquaponics has great potential as a solution for family food security in urban areas. In order to optimize this potential, policies and programs are needed that support the implementation of aquaponics as a sustainable food alternative in urban areas.